Insights on Begonia jagori (Begoniaceae), a cryptic species of Albay Province, Luzon Island, Philippines - Dela Cruz, Cyrus Job P.; Collantes, John Paul R.; Bustamante, Rene Alfred Anton; Ang, Yu Pin (Phytotaxa, 2024)
In documenting the flora of Mt. Malinao, Albay Province, Bicol region, Philippines an unknown Begonia from section Petermannia was discovered in the higher altitudes. Further study of relevant specimens and protologue identified it as Begonia jagori, a species endemic to the Philippines. Begonia jagori was known from a single collection in 1861 and since then, it has not been recollected or redocumented again. The collection locality was listed broadly as Luzon, and the protologue lacked some details. Using the materials from Mt. Malinao, the plant was redescribed and lectotypified. A note comparing its affinity to B. cumingiana is provided.